Machine learning-based methods in structural reliability analysis: A review - Saraygord Afshari, Sajad; Enayatollahi, Fatemeh; Xu, Xiangyang; Liang, Xihui (Reliability engineering & system safety, 2022)
•A review of the machine learning-based structural reliability analysis methods is presented.•Artificial neural networks-based structural reliability analysis methods are reviewed.•Support vector machines-based structural reliability analysis methods are reviewed.•The application of Bayes’ theorem for structural reliability analysis is reviewed.•The application of Kriging estimation with an active learning perspective for structural reliability analysis is reviewed. Structural Reliability analysis (SRA) is one of the prominent fields in civil and mechanical engineering. However, an accurate SRA in most cases deals with complex and costly numerical problems. Machine learning-based (ML) techniques have been introduced to the SRA problems to deal with this huge computational cost and increase accuracy. This paper presents a review of the development and use of ML models in SRA. The review includes the most common types of ML methods used in SRA. More specifically, the application of artificial neural networks (ANN), support vector machines (SVM), Bayesian methods and Kriging estimation with active learning perspective in SRA are explained, and a state-of-the-art review of the prominent literature in these fields is presented. Aiming towards a fast and accurate SRA, the ML techniques adopted for the approximation of the limit state function with Monte Carlo simulation (MCS), first/second-order reliability methods (FORM/SORM) or MCS with importance sampling well as the methods for efficiently computing the probabilities of rare events in complex structural systems. In this regard, the focus of the current manuscript is on the different models’ structures and diverse applications of each ML method in different aspects of SRA. Moreover, imperative considerations on the management of samples in the Monte Carlo simulation for SRA purposes and the treatment of the SRA problem as pattern recognition or classification task are provided. This review helps the researchers in civil and mechanical engineering, especially those who are focused on reliability and structural analysis or dealing with product assurance problems.